Afzalur Rahman's Thinking Contribution To The Islamic Economy From Epistemological Aspects To The Concept of Wages In Islam - Havis Aravik; Rahma Febrianti; Achmad Irwan Hamzani; Nur Khasanah (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2022)
This article describes the contribution of Afzalur Rahman`s thought to Islamic economics from the epistemological aspect to the concept of wages in Islam. This article is a type of library research, with the data presented being qualitative data. Data were collected from primary and secondary sources and analyzed with a qualitative descriptive method. This study's results show that Afzalur Rahman is one of the well-known Muslim economists who is very productive in producing works. Afzalur Rahman's real contribution to economics can be seen in various Islamic economic theories that were developed from the results of numerous analyzes, such as the foundation of Islamic economics built on monotheism, justice, leadership, brotherhood, work, productivity, ownership, freedom, and responsibility, social security, and prophecy. On the concept of wages, Rahman agrees that wages must be determined through negotiations between workers, employers, and the state, to provide justice for various parties.